Why Are We Here? On the (Philosophical) Value of Documents - Marco Inchingolo; Valeria Martino (Proceedings from the Document Academy, 2018)
What does a philosopher do with documents? The most natural answer to this question would probably be that philosophers, as writers, produce documents. What would appear as less intuitive, though, is a philosopher producing documents about documents. But philosophy—and in particular ontology—has always been interested in what there is out there in the world. And documents are a peculiar class of objects, the stuff the world is filled with. This year, the Annual Meeting of the Document Academy has been hosted by a philosophy department for the first time: by the Department of Philosophy of the University of Turin. This editorial introduces the proceedings from this meeting.